Interactive effects of nitrogen, UV and PAR on barley morphology and biochemistry are associated with the leaf C:N balance - Klem, K; Oravec, M; Holub, P; Šimor, J; Findurová, H; Surá, K; Veselá, B; Hodaňová, P; Jansen, M A K; Urban, O (Plant physiology and biochemistry, 2022)
Environmental conditions to which plants acclimate prior exposure to abiotic or biotic stressors can greatly affect their subsequent resilience. This may have a significant impact on the response to ongoing climate change and can be useful for increasing the food security under adverse weather conditions associated with climate change.Within this study, we tested the hypothesis that plant morphological and biochemical acclimation to radiation conditions and nitrogen (N) availability is closely linked with carbon (C) and N balance. Four barley (Hordeum vulgare) varieties, differing in their morphological characteristics and sensitivity to photooxidative stress, were grown at two levels of N supply and four radiation regimes combining distinct levels of ultraviolet (UV) and photosynthetically active radiation (PAR). Changes in root and shoot morphology, accumulation of phenolic compounds, amino acids, and sugars were studied together with the analysis of C and N content in leaves. Both UV and PAR reduced leaf length and increased root-to-shoot ratio (R:S). Such effect was more pronounced under high N availability. High N supply reduced R:S, but this effect showed significant interactions with UV and PAR, and also with barley variety. Changes in R:S were positively related to C:N ratio in leaves that varied in response to both N availability and radiation treatments. UV radiation, particularly in combination with high PAR intensity, led to increases in most phenolic compounds (particularly flavones such as saponarin, homoorientin and isovitexin) which was also closely associated with changes in C:N ratio, while specifically phenolic acids (vanillic and syringic acids) decreased under high levels of UV and PAR, and hydroxycinnamic acids responded positively mainly to PAR. Although high N availability generally reduced the accumulation of phenolic compounds, this effect was genotype-specific and modulated by the radiation regime. A similar antagonistic effect of radiation treatment and N availability was also found for the accumulation of sugars (pentoses), resulting in a close relationship between the accumulation of pentoses and C:N ratio. The accumulation of most amino acids, in contrary to phenolic compounds, increases at high N and is also stimulated by high PAR and UV intensities. We conclude that radiation conditions and N availability have opposite effects on plant morphology and accumulation of most phenolic compounds and modulate the amino acid and sugar metabolism. Strong associations of these responses with changes in C:N ratio indicates that plant stoichiometry integrates acclimation processes and induction of relevant defence mechanisms.
Keywords: ječmen (rod); ultrafialové záření; Hordeum; Plant Leaves; Amino acids; Barley; Photosynthesis; Carbon; Phenolic compounds; dusík; Ultraviolet Rays; rostliny; Plants; Root to shoot ratio; Nitrogen; Sugars; listy rostlin; fotosyntéza